Personal Data Protection for Health Data Security Governance in E-Health System - Nazwa Putri Mbuinga; Inayah R Bempah; Zalwa Natasha Anggreini Manoppo (Programs Study Outside the Main Campus in Law Pattimura University ARU Islands Regency, 2026)
Personal data, including medical information, is highly vulnerable to leaks, which can trigger various cybercrimes such as identity theft and fraud. This study uses a normative legal approach with conceptualization methods and a review of legislation to examine the challenges and solutions in implementing data protection in accordance with Law Number 27 of 2022. The research findings indicate that despite increasingly strengthened legal support, various obstacles such as low public awareness, limited law enforcement resources, and complexity remain major barriers. Therefore, it is recommended that regulations be harmonized, encryption technology implemented, and public literacy and training for healthcare providers be improved to maintain patient data privacy and security.